Desarrollo de página web y gestor de contenidos de la Institución Educativa Flowers Hill Bilingual School de San Andrés Islas (2021)
The main objective of the project is to design a web page with a news content manager for the Flowers Hill Educational Institution in the city of San Andrés based on the misinformation suffered by the educational community to disseminate the institution's activities. In addition to having the presentation of services, academic, sports and cultural activities to seek the well-being of institutional members and the entire community, this information will be disclosed and managed by a content manager and templates on the website. For related purposes, we use quantitative and qualitative perspectives to describe the characteristics and quality of the educational institution, thus strengthening the design of proposals to implement informative web pages and meet the socialization needs of the academic activities of this prestigious institution.